Life Cycle Assessment of Simulated Hydrogen Production by Methane Steam Reforming - Amran, Umarul Imran; Arshad, Ahmad; Mohamad Rizza, Othman (AENSI Publishing, 2017)
Hydrogen has attracted global attention as alternative energy carrier in the future. Typically, hydrogen is produced through methane steam reforming (MSR) followed by water gas shift (WGS) reaction. Although considered as clean energy, it is essential to assess the environmental impact of hydrogen production process which could help to compare and improve existing technology. Thus, the objective of this study is to conduct a life cycle assessment (LCA) of hydrogen production from natural gas (NG) as feedstock. In order to gain detail and extensive process inventory, a rigorous flowsheet simulation of hydrogen production was developed in Aspen Plus 8.6. The goal of LCA is to evaluate the environmental impact of all processes involved in hydrogen production from natural gas. The environmental assessment was carried out using GaBi based on ReCiPe method. The system boundaries considered for this assessment were natural gas feedstock, hydrogen production, process steam, process water plant and solvent absorption. The LCA system function is the production of hydrogen from methane while the functional unit chosen is 1 kg of hydrogen. Overall, ten life cycle impact assessment categories were carried out. Our findings show that the most contributing impact categories were climate change and resource depletion which include fossil and water.